Custo-efetividade dos análogos de nucleosídeos/nucleotídeos para hepatite crônica B - Alessandra Maciel Almeida; Anderson Lourenço da Silva; Cristina Mariano Ruas Brandão; Mariângela Leal Cherchiglia; Eli Iola Gurgel Andrade; Gustavo Laine Araújo de Oliveira; Ricardo Andrade Carmo; Francisco de Assis Acurcio
OBJECTIVE: To conduct a cost-effectiveness analysis of drug alternatives with rescue therapy in case of relapse due to viral resistance for the treatment of patients with chronic hepatitis B (CHB). METHODS: Hypothetical cohort of patients with CHB, HBeAg-negative, without clinical or histological evidence of cirrhosis, detectable HBV DNA, histological diagnosis of the disease, positive serum HBsAg for longer than six months, high levels of alanine aminotransferase (ALT) (twice as high as the upper limit of normality) and mean age of 40 years. A Markov model was developed for chronic hepatitis B (HBeAg- negative) with a 40-year time horizon. Costs and benefits were discounted at 5%. Annual rates of disease progression, costs due to complications and the efficacy of medicines were obtained from the literature. One-way and probabilistic sensitivity analysis evaluated uncertainties. RESULTS: Initiation of treatments with entecavir resulted in an increase of 0.35 discounted life-years gained compared to lamivudine. The incremental cost-effectiveness ratio was R$16,416.08 per life-years gained. In the sensitivity analysis, the incremental cost-effectiveness ratio was more sensitive to variation in the probability of transition from chronic hepatitis B to compensated cirrhosis, discount rate and medicine prices (± 10%). In the probabilistic sensitivity analysis, the acceptability curve showed that beginning treatment with entecavir was the most cost-effective alternative in comparison with the use of lamivudine. CONCLUSIONS: The availability of entecavir is economically attractive as part of early treatment for patients with chronic hepatitis B without HIV co-infection.